2002
DOI: 10.1186/1471-2350-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in human leukemic cells with or without monosomy 7 or 7q-

Abstract: Background: In bone marrow material from patients with various leukemias we noted that samples with either a deletion on the long arm of one chromosome 7 (7q-) or a monosomy 7 had a higher telomerase activity. Considering that introduction of a chromosome 7 into a cancer cell line had been reported to eliminate telomerase activity, that 7q-is a common negative prognostic finding in cancers, and that the deleted segment (band 7q31) contains an unidentified tumor suppressor gene, we wondered if this gene might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Other study done by Serakinci and Koch, (2002) also found there was no evidence of TERC gene amplification in human leukaemic cells. Our study showed almost all of study participants did not have TERC gene amplification and support the fact that haematologic disorders dissimilar from other cancers as they might originate from a cell with low-level of telomerase activity.…”
Section: Discussionmentioning
confidence: 77%
“…Other study done by Serakinci and Koch, (2002) also found there was no evidence of TERC gene amplification in human leukaemic cells. Our study showed almost all of study participants did not have TERC gene amplification and support the fact that haematologic disorders dissimilar from other cancers as they might originate from a cell with low-level of telomerase activity.…”
Section: Discussionmentioning
confidence: 77%
“…One study that included patients with different types of leukemia subgroups reported that amplification of hTERC and hTERT genes was associated with increased telomerase activity and expression in leukemia cells [12]. Hematologic malignancies differ from other cancers, as they do not originate from cells with low-level telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…FISH is a useful method for observing gene amplification and was used in the present study to determine hTERC gene amplification. Previous studies have reported that amplification of hTERT and hTERC genes in acute leukemia cells exhibit a variable number of copies-as many as 12-based on FISH analysis [12].…”
Section: Discussionmentioning
confidence: 99%